Water for energy and fuel production - Saini, Sidharth (SCITUS Academics LLC, 2016)
Energy and water are valuable resources that underpin human prosperity and are, to a large extent, interdependent. Water is ubiquitous in energy production: in power generation; in the extraction, transport and processing of fossil fuels; and, increasingly, in irrigation to grow feedstock crops used to produce biofuels. Similarly, energy is vital to the provision of water, needed to power systems that collect, transport, distribute and treat it.